Oral antidiabetic medicines and insulins in the lists of essential medicines of brazilian capitals and the federal district (Revista Contexto & Saúde, 2026)
Access to medicines is essential for the treatment of diabetes. Essential medicines lists provide knowledge of the available options and offer opportunities for rational use from several perspectives. Thus, this article aims to analyze oral antidiabetic medicines and insulins in the essential medicines lists of Brazilian capitals and the Federal District. This descriptive study was conducted through the investigation of essential medicines lists in Brazilian capitals and the Federal District. Data were collected from September to November 2022. The comparison of lists considered the 2022 National List of Essential Medicines (RENAME) and the 2021 World Health Organization (WHO) model list of essential medicines. The frequency of oral antidiabetic medicines ranged from two in Curitiba to eight in Teresina. Regarding insulins, there were six in Belo Horizonte, while Boa Vista, Macapá, Fortaleza, and João Pessoa did not include them. Metformin was the most frequently used oral antidiabetic medicine, as were NPH and regular insulins. The average agreement of oral antidiabetic medicines and insulins with the RENAME was 97.7% and 75.5%, respectively. The average agreement of oral antidiabetic medicines was 47.1% and 72.5% for insulins with the WHO model list of essential medicines. We observe a diversity in the range of medicines available for diabetes. Lists of essential medicines are guiding instruments for pharmaceutical services, and the lack of a description of insulins proved to be a cause for concern.
Keywords: Diabetes Mellitus; Drugs; Essential; Access to Essential Medicines and Health Technologies; Hypoglycemic Agents; Insulin